Techno-Optimism and Rational Superstition. - Wilson, Alexander (Techné: Research in Philosophy & Technology, 2017)
This article examines some of the implications of technological optimism. I first contextualize, historically and culturally (Christopher Nolan's Interstellar [2014] is considered as a particularly salient example), some contemporary variants of techno-optimism in relation to the equally significant contemporary exemplars of techno-pessimism, skepticism and fatalism. I show that this techno-optimism is often instrumentalized in the sense that the optimistic outlook as such is believed to have some influence on the evolving state of affairs. The cogency of this assumption is scrutinized. I argue that in the absence of explicit probabilities, such optimism presupposes some form of retro-causation, where the future is held to somehow have a retroactive effect on the past. This suggests that the underlying mechanism by which techno-optimism is supposed to be instrumental in bringing about the future is fundamentally superstitious. Such superstition, of course, goes against our common understanding of reason and rationality, for adopting rational expectations about the world requires that we avoid the emotional over-determination of our assessments. I show that applied reason is conceptually entangled with this superstitious optimism in the continued successes of technology. The article thus reveals a curious sense in which reason is intrinsically superstitious. I offer an evolutionary explanation for this, showing that the biological origins of reason will by nature tend to produce rational agents which are superstitiously bound to realism and causality, and thus implicitly optimistic about technology's capacity to overcome contingency.